Clinical presentation of prostate cancer in Black South Africans - Tindall, Elizabeth A.; Monare, L. Richard; Petersen, Desiree C.; van Zyl, Smit; Hardie, Rae-Anne; Segone, Alpheus M.; Venter, Philip A.; Bornman, M.S. Riana; Hayes, Vanessa M. (The Prostate, 2014)
BACKGROUND Compared with White Americans, Black American men are at a significant increased risk of presenting with prostate cancer (PCa) and associated mortality, suggesting a link to African‐ancestry. However, PCa status within Africa is largely unknown. We address the clinical presentation of PCa within Black South African men. METHODS Over 1,000 participants with or without PCa have enrolled in the Southern African Prostate Cancer Study (SAPCS). Using genome‐wide profiling we establish a unique within Africa population substructure. Adjusting for age, clinical variables were assessed, compared against Black Americans and between rural and urban localities while addressing potential socio‐demographic confounders. RESULTS We report a significant difference in the distribution of prostate specific antigen (PSA) levels skewed towards higher PSA levels in the PCa cases (83.0% present with a PSA ≥ 20 µg/L; median PSA = 98.8 µg/L) relative to men with no detectable PCa (18.5% present with a PSA ≥ 20 µg/L; median PSA = 9.1 µg/L). Compared with Black Americans, Black South Africans presented with significantly more aggressive disease defined by Gleason score >7 (17% and 36%, respectively) and PSA ≥ 20 µg/L (17.2% and 83.2%, respectively). We report exasperated disease aggression defined by Gleason score >7 (P = 0.0042) and poorly differentiated tumor grade (P < 0.0001) within rural versus urban localities. CONCLUSION Black South African men present with higher PSA levels and histopathological tumor grade compared with Black Americans, which is further escalated in men from rural localities. Our data suggests that lack of PSA testing may be contributing to an aggressive PCa disease phenotype within South African men. Prostate 74:880–891, 2014. © 2014 The Authors. Prostate published by Wiley Periodicals, Inc.